A Rare Case of Infliximab-Induced Small Vessel Vasculitis With Renal Involvement - Anna Way MD; Elena Weinstein MD (SAGE Publishing, 2023)
There are few cases in the literature demonstrating vasculitis induced by tumor necrosis factor-α. There exist even fewer cases of systemic inflammation involving the skin, nerves, and kidneys. Here, we present a novel case of a 27-year-old man with Crohn disease refractory to multiple medications, most recently treated with infliximab. He presented with a 3-week history of non-blanching palpable petechial rash involving his bilateral extremities and right upper extremity as well as lesions with black eschar around his ankles. He was found to have refractory cutaneous small vessel vasculitis, nephrotic range proteinuria, and small fiber neuropathy. This case describes the evaluation and treatment of systemic small vessel vasculitis in the setting of infliximab therapy.